Neurosurgery practice questions and answers - Shaya, Mark; Gragnaniello, Cristian; Nader, Remi (Thieme, 2016)
Comprehensive, but small enough to take on rounds, the updated second edition of this popular neurosurgical board review provides a robust study companion for the American Board of Neurological Surgery (ABNS) primary examination. The text includes an impressive number of questions with concise and well-delineated explanations. Suitable for thorough board preparation, the question and answer format enables busy neurosurgical residents to efficiently practice, review, and improve upon their comprehension. In addition to all the fundamental disciplines that are relevant to the practice of neurosurgery, this edition encompasses the latest advances in the field including endovascular approaches, minimally invasive spinal surgery techniques, and genetics. The diverse and challenging questions encourage the acquisition of factual knowledge and application of logic. This is the definitive ABNS study book because it most closely mimics the written board examination format.